Analisis Investasi Sektor Energi Terbarukan Terhadap Keberlanjutan Ekonomi Pembangunan Nasional di Era Globalisasi - Satria Lam Syafi’i Simamora; Imsar Imsar (Journal Economic Excellence Ibnu Sina, 2025)
This research employs a qualitative library research method to examine the crucial role of investment in the renewable energy sector in sustaining national economic development in the globalization era. In the current global context, the transition toward environmentally friendly energy sources is not only a necessity but also a strategic priority for many countries, including Indonesia. Conventional reliance on fossil fuels, which are increasingly limited and harmful to the environment, has pushed policymakers and stakeholders to seek sustainable alternatives. Renewable energy sources—such as solar, wind, hydro, and bioenergy—are widely recognized as long-term solutions to reduce environmental degradation and carbon emissions. Investment in the renewable energy sector does not merely contribute to environmental preservation but also carries significant socioeconomic benefits. It has the potential to generate new employment opportunities, encourage technological innovation, and strengthen national energy security. These impacts create a multiplier effect on the economy, thereby supporting inclusive growth and sustainable development. Furthermore, renewable energy investment can enhance national competitiveness and resilience in facing global energy transitions, as well as align with international commitments to climate change mitigation. This study, through a comprehensive review of scholarly journals, reports, and other credible sources, finds that the renewable energy sector is instrumental in realizing a sustainable and globally adaptive economic structure. Nevertheless, the success of this transition depends heavily on government efforts to optimize policies and regulatory frameworks that are supportive, transparent, and attractive to both domestic and international investors. Therefore, it is imperative for the government to strengthen investment incentives, streamline bureaucratic procedures, and promote public-private partnerships. The findings highlight that renewable energy investment is not only an environmental necessity but also a key driver of long-term national economic sustainability.